PENGARUH LINGKUNGAN BELAJAR DAN GAYA BELAJAR TERHADAP KUALITAS BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SEKOLAH MENENGAH PERTAMA NEGERI 22 BATANG HARI - Atika Dhanasari; Ahmad Ridwan; Zawaqi Afdal Jamil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of learning environment and learning styles on the learning quality of Islamic Religious Education (PAI) students at SMP Negeri 22 Batang Hari. This research employed a quantitative approach with an associative research design using a survey method. The population consisted of 160 students, while the sample included 114 students. Data analysis was conducted using SPSS software. The results showed that the learning environment had a significant effect on students’ learning quality in PAI, with a significance value of 0.003 < 0.05, thus the first hypothesis (H1) was accepted. The effect was positive, indicating that a better learning environment leads to an improvement in students’ learning quality. Learning styles were also found to have a significant effect on learning quality, with a significance value of 0.023 < 0.05, so the second hypothesis (H2) was accepted; however, its influence was relatively weaker compared to the learning environment. Furthermore, both learning environment and learning styles simultaneously had a significant effect on learning quality, with a significance value of < 0.001 < 0.05, thus the third hypothesis (H₃) was accepted. The coefficient of determination (R Square) was 0.127 or 12.7%, while the remaining 87.3% was influenced by other variables not included in this study. Keywords: learning environment, learning styles, learning quality, Islamic Religious Education.